2017
DOI: 10.1111/mcn.12452
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency causes rickets in an urban informal settlement in Kenya and is associated with malnutrition

Abstract: The commonest cause of rickets worldwide is vitamin D deficiency, but studies from sub‐Saharan Africa describe an endemic vitamin D‐independent form that responds to dietary calcium enrichment. The extent to which calcium‐deficiency rickets is the dominant form across sub‐Saharan Africa and in other low‐latitude areas is unknown. We aimed to characterise the clinical and biochemical features of young children with rickets in a densely populated urban informal settlement in Kenya. Because malnutrition may mask … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
2
26
0
1
Order By: Relevance
“…The finding that clinically defined rickets was associated with baseline stunting and wasting agrees with previous reports (H. L. Jones et al, 2015). In our study, clinical rickets cases were predominantly from urban sites as previously reported (Edwards et al, 2014;K. D. J. Jones et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The finding that clinically defined rickets was associated with baseline stunting and wasting agrees with previous reports (H. L. Jones et al, 2015). In our study, clinical rickets cases were predominantly from urban sites as previously reported (Edwards et al, 2014;K. D. J. Jones et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The finding that clinically defined rickets was associated with baseline stunting and wasting agrees with previous reports (H. L. Jones et al, ). In our study, clinical rickets cases were predominantly from urban sites as previously reported (Edwards et al, ; K. D. J. Jones et al, ). Other studies, although not among children hospitalized with complicated SAM, have found evidence of association between vitamin D deficiency and severe pneumonia, gastrointestinal infection, and growth (Ganmaa et al, ; Haider et al, ; Muhe et al, ; Thornton et al, ).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations